2011
DOI: 10.1108/03699421111180554
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of new antioxidants for styrene butadiene rubber

Abstract: PurposeThe purpose of this paper is to study the effect of new heterocyclic compounds on styrene butadiene rubber (SBR) mixes.Design/methodology/approachIt has been found that the starting material 1 could react with cyromazine (2) and/or 4‐aminoantipyriene (4) as amino compounds in the presence of triethylorthoformate and in the boiling dioxane to yield triazine‐3 and/or pyrazolo 5 derivatives, respectively. The chemical structures of the new products 3 and 5 have been established by their elemental analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Antimicrobial activity [6][7][8] The newly synthesized compounds were screened for their antibacterial activity against Escherichia coli (Gram negative bacteria) and Staphylococcus aureus (Gram positive bacteria) by the disc diffusion method, and for their antifungal activity against Aspergillus flavus and Candida albicans in DMSO by the agar diffusion method.…”
Section: For 5aez Protein the Amino Acids Hydrogen Bond And Energymentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial activity [6][7][8] The newly synthesized compounds were screened for their antibacterial activity against Escherichia coli (Gram negative bacteria) and Staphylococcus aureus (Gram positive bacteria) by the disc diffusion method, and for their antifungal activity against Aspergillus flavus and Candida albicans in DMSO by the agar diffusion method.…”
Section: For 5aez Protein the Amino Acids Hydrogen Bond And Energymentioning
confidence: 99%
“…[1-3] 2-Cyanoacetamide moieties have found as vital synthons in the synthesis of many active biological heterocyclic systems such as quinoxalinones, pyridines, thiazoles and pyrimidines. [4][5][6][7][8][9] So, our interested work herein is focusing on using N-(4-substitutedphenyl)-2-cyanoacetamide 1a-c as valuable synthons in the synthesis of simple active heterocyclic compounds and evaluate the resulted compounds as antimicrobial agents against strains of Escherichia coli (Gram negative bacteria) and Staphylococcus aureus (Gram positive bacteria) by the disc diffusion method [10,11] together with strains of fungi Aspergillus flavus and Candida albicans [12] by the agar diffusion method.…”
Section: Introductionmentioning
confidence: 99%
“…So it can be concluded that MPM is an interesting antioxidant for SBR vulcanizates. Table 4 shows the SBR mixes which vulcanized to their T C90 at [18][19][20][21]. Figures 7-10 show the physico-mechanical properties of SBR vulcanizates as strength at break, modulus at 100% and 200%, and elongation at break against the aging time.…”
Section: Influence Of Mpm As Anti-thermal Aging On the Nr Vulcanizatesmentioning
confidence: 99%
“…Their chemical and physical properties recommend them as engineering materials for chemical industry, electric insulators, and many other uses. 1 6 The wide range of applications of rubber from footwear to automobile tires comes from their individual mechanical characteristics, such as good flexible attitude even at great distortion and good energy absorbing capability.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The tire industry depends on the SBR for its meritorious properties such as good incision impedance, humidity, and weather resistance. 6,8 Moreover, it is used for other various applications, including membranes, wires, and cables. 9 11…”
Section: Introductionmentioning
confidence: 99%